Modern Greek Constructions with Position Verb κάθομαι - E. S. Onufrieva (Научный диалог, 2023)
The article analyzes the functioning of the Modern Greek verb κάθομαι ‘to sit’ in relation to its lexical and syntactic environment. The study is motivated by the under-researched system of position verbs in Modern Greek and their grammaticalization. Corpus and lexicographic methods are used, drawing on data from the National Corpus of Greek and the elTenTen19 corpus, as well as major Modern Greek dictionaries. The spectrum of meanings of κάθομαι is analyzed, along with the constructions in which these meanings are manifested. A corpus analysis of the construction Τι κάθεσαι και Χ is separately conducted. The study shows that κάθομαι is a weakly semantically-specified lexical unit whose meaning is determined by its context. In the construction Τι κάθεσαι και Χ, which expresses a negative evaluation of an action or state X, the verb κάθομαι loses its meaning of a specific human posture. However, depending on the lexical content of the construction slot, it is capable of demonstrating various non-locative meanings within the same construction. The interaction between κάθομαι as a constituent element of the construction and the lexical content of the slot allows this verb to exhibit its polysemy.